CHILDREN'S SOCIAL VALUES: SINGLE MOTHER PARENTING - Veryawan Veryawan; Juliati Juliati (Journal of Gender and Social Inclusion in Muslim Societies, 2022)
Parenting by single mothers is one of the most common social phenomena in society. Parents become single parents due to several factors such as the occurrence of divorce and or their spouse has died. Parents who become single parents will experience a series of problems. This is because there is only one parent who cares for and raises the child. The purpose of this study is to find out how the parenting style is, the inhibiting factors and to find out the efforts of single mothers in instilling social values in children. The approach taken in this research is a qualitative approach. The data collection technique used in this research is to use the method of observation, interviews and documentation. In addition, the data analysis technique uses the data triangulation method for data reduction, data presentation and drawing conclusions. The results of this study are, single parent parenting in instilling social values in children uses democratic and authoritarian parenting styles. Where a single parent democratic parenting pattern always prioritizes the interests of children, nurturing them with love without any coercion, the inhibiting and encouraging factors in instilling social values in children in the area are busyness factors and economic factors and low economic factors where parents busy working so that it is difficult to instill social values in children, and the efforts made by single mothers with good communication between single parents and children can have a positive impact on children's morale because parents' advice or messages are conveyed to children in instilling children's social values.